Out-of-Field Teaching in Craft Education as a Part of Early STEM: The Situation at German Elementary Schools - Johanna Beutin; Mona Arndt; Stefan Blumenthal (Education Sciences, 2025)
The shortage of skilled professionals in technical fields is further compounded by a lack of qualified teachers in STEM subjects, particularly in craft education, which is vital for developing technical competencies at the elementary level. The present study investigates the professionalisation of teachers in craft education and explores the prevalence and reasons for out-of-field teaching across three German federal states. The data presented herein were collected through an online survey administered in 2023 among teaching professionals in Mecklenburg-Vorpommern, Sachsen, and Thüringen. The questionnaire was disseminated via head teachers to 1467 elementary schools, yielding a self-selection sample of 284 craft education teachers. The survey incorporated both closed- and open-ended questions, encompassing inquiries into teacher qualifications, subject-specific competence, and lesson planning. Quantitative data were analysed descriptively. The evaluation of open-ended responses employed a content-structuring content analysis approach, utilising categories that were inductively developed. The findings indicate that a considerable proportion of craft education is taught by educators who lack formal qualifications, thereby giving rise to concerns regarding the quality of instruction. The underlying factors contributing to this phenomenon include teacher shortages, personal interests, prior experience, and limited professional development opportunities. The findings emphasise the pressing necessity for enhanced teacher education and targeted training programmes to bolster instructional quality in technically oriented subjects.